(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Women Entrepreneurship play an important role in an economic growth. In India, though women are playing key role in the society but still their entrepreneurial ability has not been properly tapped due to the lower status of women in the society. In man oriented society, women want to prove him and created equality and democratic approachand also discusses various programs taken by government for women entrepreneurship development. This paper has been made to study about the status of women entrepreneurs and the challenges faced by them when they set up and managed their own businesses of business environment. This study is based on secondary data and primary data which is collected through questionnaire among 100 respondents in Madurai and data were analysed the reasons behind women entrepreneurs’ success and failures withHentry Garret Rankingwere used to identify themInfluencing factors on women Entrepreneurs and how to overcome that.